2019
DOI: 10.1530/eje-18-0923
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant mitotane therapy is beneficial in non-metastatic adrenocortical carcinoma at high risk of recurrence

Abstract: Objective Many patients with adrenocortical carcinoma (ACC) suffer from tumor recurrence despite radical surgery. Evidence on the post-operative use of mitotane is controversial and no predictors of response are available. We aimed to assess whether adjuvant mitotane treatment may prolong survival in patients with non-metastatic ACC following complete resection and whether ACC patients at high risk of recurrence may benefit from treatment. Design and methods We retrospectively reviewed data from 152 non-meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…Moreover, the administration of adjuvant mitotane treatment to most of our patients with a high risk of tumour recurrence (ie Ki‐67 > 10%) probably had beneficial impact on the rate of tumour recurrence. This is in accordance with the recent study by Calabrese et al who demonstrated that adjuvant mitotane treatment might prolong RFS in ACC patients after radical tumour resection 20 . Furthermore, all patients from our cohort for whom the data on blood mitotane level were available reached and maintained the target mitotane concentration >14 mg/L which has been shown to be associated with a favourable response to adjuvant mitotane treatment 21 …”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the administration of adjuvant mitotane treatment to most of our patients with a high risk of tumour recurrence (ie Ki‐67 > 10%) probably had beneficial impact on the rate of tumour recurrence. This is in accordance with the recent study by Calabrese et al who demonstrated that adjuvant mitotane treatment might prolong RFS in ACC patients after radical tumour resection 20 . Furthermore, all patients from our cohort for whom the data on blood mitotane level were available reached and maintained the target mitotane concentration >14 mg/L which has been shown to be associated with a favourable response to adjuvant mitotane treatment 21 …”
Section: Discussionsupporting
confidence: 93%
“…Further support for adjuvant mitotane came from another recent retrospective study that included 152 patients with non-metastatic ACC (100 patients who received adjuvant mitotane and 52 who did not receive adjuvant therapy) who were stratified by disease stage (I-II vs III), hormone secretion (yes vs. no), and Ki-67 index. The recurrence risk was greater in patients who did not receive mitotane (HR, 2.79; 95% CI, 1.58-4.91) compared with those who did, but OS did not differ significantly between groups [59].…”
Section: Adjuvant Mitotanementioning
confidence: 88%
“…Cancers 2020, 12, x 6 of 12 mitotane (HR, 2.79; 95% CI, 1.58-4.91) compared with those who did, but OS did not differ significantly between groups [59].…”
Section: Adjuvant Mitotanementioning
confidence: 94%
“…The topic of mitotane toxicity is of clinical interest considering that mitotane is still the backbone therapy for advanced ACC [15] and that the drug is also recommended as an adjuvant measure in ACC patients at high risk of recurrence following radical surgery [13,[20][21][22][23][24]. Drug toxicity is a compelling issue particularly in the adjuvant setting, since it may be more difficult to justify treatment-related problems in patients who are free of disease.…”
Section: Discussionmentioning
confidence: 99%